Abatement by Alhagi maurorum of lead-induced nephrotoxicity in rats: emphasis on Nrf2/HO-1 - Mardi M. Algandaby (Future Journal of Pharmaceutical Sciences)
Abstract Background Lead (Pb) is a heavy metal with extreme toxicity and numerous industrial uses. It produces nephrotoxicity with notable changes in renal architecture and function. The Alhagi maurorum (AM) belongs to the family Fabaceae and is native to the Middle East area. In the present study, the potential nephroprotective effects of AM in Pb-intoxicated rats were evaluated. Results AM methanolic extract was standardized in reference to its main phenolic compounds orientin, rutin, and quercetin. Acute oral toxicity studies indicated that the extract is safe for animals. Rats were allocated into five groups and treated for 28 days as follows: control, AM (200 mg/kg, orally), Pb (15 mg/kg, orally), Pb + AM (100 mg/kg), and Pb + AM (200 mg/kg). Pb administration markedly increased serum cystatin C, urea, creatinine levels, and urinary NAG. Pb also caused renal histopathological alterations. However, AM o-treatment ameliorated such pathological changes. In addition, AM treatment prevented Pb-induced accumulation of malondialdehyde (MDA), attenuated glutathione (GSH) depletion, and catalase (CAT) and superoxide dismutase (SOD) exhaustion. AM guarded against Pb-induced enhanced the protein expression of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), cyclooxygenase-2 (COX-2), and nuclear factor-kappa B (NF-κB). Further, AM significantly prevented Pb-induced upregulation of mRNA levels of Bax and downregulation of Bcl-2. These effects were associated with increased levels of heme oxygenase-1 (HO-1) and nuclear factor erythroid 2-related factor 2 (Nrf2) in renal tissue. Conclusion AM guards against Pb-induced nephrotoxicity in rats that involve, at least partly, the antioxidant, anti-inflammatory, and anti-apoptotic activities as well as the modulation of HO-1 and Nrf2 expression.